KONSEP PENDIDIKAN MULTIKULTURAL DALAM MENCIPTAKAN SISTEM KELEMBAGAAN YANG HARMONI - Roro Kurnia Nofita Rahmawati; Mufiqur Rahman (Universitas Islam Lamongan, 2019)
This artickel discussed that institution would stay survived harmony throught social conruction Pierre Boudieu with cultural capital, economy capital, and symbolic capital. The consept of educational multicultur need those capitals to creat harmony institution, tolerance as the values of educational multicultur. So the the bia idea cuntructed by Maskuri in this artickel is fixed with the concepts of the theory of Abraham Maslow, Talcott person, pieree Boudiou that given a new perceptions on how to creat and to build the harmony institution system based on the multicultural education.